Aktualisasi Nilai ANEKA pada Profesi Dosen IHDN Denpasar Sebagai Dasar Komitmen Mutu Pelayanan Publik - Putu Santi Oktarina (Jurnal Penjaminan Mutu, 2016)
Apparatus profession as a lecturer in the Civil State plays an important role in improving the quality of the institution's commitment. Hindu Dharma Institute Denpasar State that has a vision leader in Dharma, Widya and Cultural expects all institutions including structural staff and functional staff, the lecturers, able to actualize the value of accountability, nationalism, public ethics, commitment to quality, and anti-corruption in the implementation of their obligations. However, a very small number of lecturers who have demonstrated commitment in improving public services especially for students. Therefore, through this paper, some activities were designed in internalizing the values of ANEKA.